RETRACTED: Treatment of cows with rumen atony - Smolentsev Sergey; Gracheva Olga; Mukhutdinova Dina; Gasanov Alizade; Shageeva Alfiya; Hairullin Damir; Gertman Alexander; Naumova Olga; Maksimovich Dina; Rodionova Irina; Tsugkieva Zarema; Persaeva Nadezhda; et al. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001